Honorary Members (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
1913. FRANK DAWBON ADAMS Montreal, Canada. 1921. WILLIAM CUTHBERT BLACKETT Sacriaton, Durham. England. 1923. GELAEIIO CAETANI Rome, Italy 1920. HENRY STURQIB DRINKER Merion Station, Pa, 1922. FEDERICO GIOLITTI Torino, Italy. 1906. SIR ROBERT A. HADFIELD London, England. 1928. JOHN HAYB HAMMOND New York, N. Y. 1921. FRANK WILLIAM HARBORD London, England. 1917. HERBERT HOOVER Washington, D. C. 1905. HENRI LECHATELIER Paris, France. 1931. WALDEMAR LINDQREN Cambridge, Mass. 1929. JOHN MARKLE New York, N. Y. 1921. C. MCDERMID London, England. 1913. EZEQUIEL ORDONEZ Mexico City, Mexico. 1909. ALEXANDRE POURCEL Paris, France. 1911. ROBERT H. RICHARDS Cambridge, Mass.